Sodium-glucose co-transporter-2 inhibitor (SGLT2i) treatment and risk of osteomyelitis: A pharmacovigilance study of the FAERS database - Zhao, Hui; Li, Zi-Ran; Zhang, Qian; Zhong, Ming-Kang; Yan, Ming-Ming; Qiu, Xiao-Yan (Frontiers in Pharmacology, 2023)
Background and purpose: Several clinical trials have indicated that the use of canagliflozin increases the risk of lower extremity amputation. Although the US Food and Drug Administration (FDA) had withdrawn its black box warning amputation risk on canagliflozin, but this risk still exists. We sought to estimate the association between hypoglycemic medications especially sodium-glucose co-transporter-2 inhibitors (SGLT2i) and adverse events (AEs) prior to the irreversible outcome of amputation as promising early warnings, based on the FDA adverse event reporting system (FAERS). Methods: Publicly available FAERS data were analyzed using reporting odd ratio (ROR) method and validated by Bayesian confidence propagation neural network (BCPNN) method. The developing trend of ROR were revealed by series of calculation based on accumulating dataset quarter by quarter. Results: Ketoacidosis, infections, peripheral ischemia, renal impairment, inflammation including osteomyelitis might more likely to occur among SGLT2i users, especially canagliflozin. Osteomyelitis and cellulitis are AEs unique to canagliflozin. Among 2,888 osteomyelitis-related reports referring to hypoglycemic medications, 2,333 cases were associated with SGLT2i, mostly with canagliflozin counting 2,283 which generated an ROR value of 360.89 and a lower limit of information component (IC025) of 7.79. No BCPNN-positive signal could be generated for drugs other than insulin, canagliflozin. Reports referring to insulin could generate BCPNN-positive signals during the entire timespan from 2004 to 2021, while BCPNN-positive signal emerged since second quarter (Q2) of 2017, four years since the approval of SGLT2i in Q2 of 2013, for canagliflozin and drug groups containing canagliflozin. Conclusion: This data mining investigation revealed that strong association between canagliflozin treatment and developing osteomyelitis which might be a crucial warning to lower extremity amputation. Further study with updated data is needed to better characterize the risk of osteomyelitis associated with SGLT2i.